Evaluation of the Compliance of Urban Functions in Sofia City with the 15-minute City Concept - D. Petrova-Antonova; B. Monticelli; S. Ilieva (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The rapid growth of urbanisation has led to the expansion of cities, often resulting in reduced accessibility to essential services, particularly in peripheral areas. The "15-minute city" concept proposes a decentralised urban model where residents can access amenities within a 15-minute walk. While extensive research has explored the 15-minute city model, a standardised methodology for evaluating compliance remains absent. Existing studies predominantly rely on either survey-based assessments or algorithmic approaches, often overlooking the integration of both methods and the micro-scale walkability factors that impact accessibility. This study presents a novel methodological framework for assessing urban alignment with the 15-minute city concept through an integrated qualitative and quantitative analysis. A 15-Minute City Compliance Index (15-MCCI) is introduced, comprising two components: 15-MCCI (Macro), which evaluates accessibility, and 15-MCCI (Micro), which assesses micro-scale walkability factors. The methodology utilises proximity analysis and fuzzy logic to determine compliance at the residential building level. A survey was conducted in the city of Sofia, Bulgaria, to establish key parameters such as amenity importance, preferred walking distance, and diversity thresholds. The framework was applied for the compliance assessment of the Lozenets district of the city, demonstrating spatial variations in compliance levels and the relationship between macro-scale accessibility and micro-scale walkability. Results indicate that established urban areas exhibit higher compliance due to greater amenity density and pedestrian-friendly infrastructure, whereas newly developed areas face accessibility challenges.